Acute pharmacological effects of α-PVP in humans: a naturalistic observational study - De la Rosa, Georgina; Papaseit, Esther; Hladun, Olga; Poyatos, Lourdes; Caicedo, Dolly Andrea; Argote, Martha Catalina; Martín, Soraya; Ventura, Mireia; La Maida, Nunzia; Di Trana, Annagiulia; Graziano, Silvia; Pichini, Simona; et al. (Frontiers in Pharmacology, 2025)
IntroductionAlpha-pyrrolidinopentiophenone (α-PVP) is a commonly consumed analogue of pyrovalerone, a synthetic cathinone with psychostimulant properties similar to those of 3,4-Methylenedioxypyrovalerone (MDPV) and cocaine. Since the pharmacology of α-PVP remains scarcely studied, we aimed to evaluate the acute pharmacological effects and its abuse potential in humans after intranasal administration.MethodsWe carried out a non-controlled observational study in a naturalistic environment in nine participants (3 women and six men) with a previous history of psychostimulant use. Participants self-administered a single intranasal dose of 10mg or 20mg of α-PVP. The outcomes included physiological effects (systolic and diastolic blood pressure, heart rate, and temperature) and subjective effects (Evaluation of Subjective Effects of Substances with Abuse Potential questionnaire_VESSPA-SSE, the short form of the Addiction Research Center Inventory questionnaire_ARCI and visual analog scales_VASs) and were measured at different time points (0, 20 and 40 minutes and 1, 1.5, 2, 2.5, 3, 4 and 5 hours).ResultsAn acute increase in blood pressure and heart rate was observed that peaked 40 minutes after administration. Subjective effects also showed a rapid onset and disappeared 3 to 5 hours after administration.Discussionα-PVP showed psychostimulant properties similar to those displayed by cocaine and empathogenic effects commonly associated with MDMA and other cathinones (eg. methylone) consumption.